Pelatihan Online Marketing untuk Produk Unggulan pada Organisasi Pembinaan Kesejahteraan Keluarga (PKK) di Desa Palaan Kecamatan Ngajum Kabupaten Malang - Ismi Iftikad; Aldy Rostyawan; Erna Resmiatini (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2022)
Partners in this community service activity are the Family Welfare Development Organization (PKK), whose gender members are women and the daily profession of most housewives, where they have the potential to be empowered. The basic justification is that they often receive product-making training from institutions, so that PKK members can be classified as skilled workers. However, problems arise in a group of people with the same skills and living in one area, the problem is the difficulty in selling their work because the community is able to make the same product (as a result of generic training from institutions). Armed with wanting to solve this problem, the community service team tried to help by providing an understanding of online marketing as a medium for selling and promoting their products to a wide audience (outside their village area). In this way, the problem of product sales is resolved and new entrepreneurs from the Palaan village community will emerge. The benefits that PKK members get after this activity include the ability to manage online shops, the ability to transact online, and skills in using social media as promotional media